Review articleSweet and hot heart of type 1 diabetic patient - Zozulińska, Dorota; Naskręt, Dariusz; Wierusz-Wysocka, Bogna (Przegląd Kardiodiabetologiczny/Cardio-Diabetological Review, 2007)
Coronary heart disease is a main cause of preamature death in type 1 diabetic patients. Atherosclerosis is more expensive and aggressive in diabetes and is related to duration of diabetes, occurrence of microangiopathy, hypertension, lipid abnormalities, smoking and advanced nephropathy, and renal failure. Hyperglycemia and inflammation play a key role in the development of late diabetic complications. This article is dedicated of the sweet and hot heart that stop beat too early.